2018
DOI: 10.1021/acs.energyfuels.7b03908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Process Hydrogenation on Mesophase Development during the Thermal Condensation of Petroleum Aromatic-Rich Fraction

Abstract: In this work, the mesophase pitch was generated from the thermal condensation of the petroleum aromatic-rich fraction. Tetrahydronaphthalene as a hydrogen donor was selected to treat the condensation intermediate using the in-process hydrogenation method. The objective of this work was to investigate the effects of in-process hydrogenation on the formation and development of mesophase structures. Results showed that the intermediate after in-process hydrogenation possessed a more-uniform molecular structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Hydrogen transfer reactions are very important during thermal conversion of heavy oils, bitumen, and coals. In the literature, much emphasis was placed on hydrogen donors and hydrogen donor solvents. The use of hydrogen donor solvents gave rise to the development of aptly named processes such as the Donor Refined Bitumen process, and the Exxon Donor Solvent process . A common feature of these liquefaction-type processes was the use of hydrogen donor solvents, which could be regenerated in situ or ex situ by hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen transfer reactions are very important during thermal conversion of heavy oils, bitumen, and coals. In the literature, much emphasis was placed on hydrogen donors and hydrogen donor solvents. The use of hydrogen donor solvents gave rise to the development of aptly named processes such as the Donor Refined Bitumen process, and the Exxon Donor Solvent process . A common feature of these liquefaction-type processes was the use of hydrogen donor solvents, which could be regenerated in situ or ex situ by hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the contents of alkyl chains and methylene bridges in the three intermediates were similar, but the contents of naphthenic structures increased signicantly with the rising degree of the in-process hydrogenation. 30,35 To sum up, the in-process hydrogenation was conductive to the decrease of intermediates' condensation degrees and the increase of intermediates' naphthenic structures. Given the solubility and hydrogen distribution analyses of intermediates, the increase of the naphthenic structures in intermediate was the reason for the change of the intermediates' molecular structures and extracted component distributions.…”
Section: Resultsmentioning
confidence: 99%
“…It implied that the molecules of the intermediates were increasingly concentrated in the two middle components with rising degree of the in-process hydrogenation. Furthermore, according to similarity-intermiscibility theory, 30,34 the molecules which were concentrated in components HI-TS or TI-QS possessed similar molecular structures. Therefore, the molecular structure of hydrogenated intermediate was more uniform, and the uniform degree of molecular structure increased with rising degree of the in-process hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations